MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN PADA ANAK TUNARUNGU - Aulia - Resti (Jurnal Penelitian Pendidikan Khusus, 2012)
The research was carried out on a deaf child, from child observations encountered in reading fluently, but in reading comprehension, the ability of children is low, look and answered many were emptied. Thus the researchers want to improve kids' reading comprehension through reading techniques stuffing tunagrungu hiatus. Type of research is the design of Single Subject Research A - B. Target size by the percentage of their behavior, children were told about the test menkawab reading comprehension skills, and researchers recorded the results and are calculated using a percentage, what percentage of children can answer the questions given. Data were analyzed using visual analysis of the graph that consists of the analysis of the condition and between conditions.